Small molecule TKI inhibitors affect the development of non-small cell carcinoma through HIPPO/YAP/PD-L1 - Lei, Li; Weidong, Zhang (Cellular and Molecular Biology, 2022)
Non-small cell lung cancer accounts for approximately 80% 85% of lung cancer (1, 2). With the rapid development of medical technology, targeted therapy is a common choice in treatment plans due to its low toxicity and high pertinence (3). EGFR can reduce the possibility of autophagy by activating downstream factors such as P13K and MAPK (4, 5). TKI inhibitors are targeted therapies for EGFR receptors, which bind to receptor target genes to block downstream pathways and improve tumor development (6, 7). Low expression of membrane proteins on PD-1T cells is an important molecule in regulating the autoimmune system (8, 9). Existing literature shows that the expression of PD-L1 is increased in tumor patients, and this protein can combine with PD-1, resulting in the occurrence of immune escape (10). The activation of YAP can be involved in tumor development. Studies have confirmed that the increased expression of YAP in serum and tissues of lung cancer patients can promote cell proliferation and metastasis (11, 12), so most drugs can inhibit tumor proliferation through HIpo-YAP. At present, there are few studies on TKI inhibition and its relationship with HIpo-YAP or PD-L1 at home and abroad. Therefore, in order to explore the correlation among the three and provide a reference for clinical drug use, this study took non-small cell lung cancer A549 cell line as the research object to explore the relationship between the influence of small molecule inhibitors on the development of non-small cell carcinoma and HIPPO/YAP/PD-L1 signaling pathway, so as to provide a basis for tumor targeting and immunotherapy. The results are as follows.